2019
DOI: 10.1080/1028415x.2019.1695360
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the essential amino acid L-tryptophan reduces masticatory impairments in experimental cerebral palsy

Abstract: Purpose Children with cerebral palsy (CP) often exhibit difficulties in feeding resulting from deficits in chewing. This study investigates the therapeutic potential of Ltryptophan (TRI) to reduce deficits in chewing in rats subjected to an experimental model of CP. Methods A total of 80 Wistar albino rats were used. Pups were randomly assigned to 4 experimental groups: Control Saline, Control TRI, CP Saline, and CP TRI groups. The experimental model of CP was based on the combination of perinatal anoxia assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Our study shows that perinatal anoxia in combination with sensorimotor restriction of the hindlimbs during infancy significantly impacts the body phenotype of rats, reducing body weight and body length during the neonatal period. Previous studies have also observed such effects in rats during exposure to a CP model (da Silva et al, 2016;Lacerda et al, 2017;Lacerda, Manhães-de-Castro, Gouveia, et al, 2019). Lacerda, Manhães-de-Castro, Gouveia et al (2019) suggested that the model's impact on these parameters may be related to motor deficits that impair access to lactation and food.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our study shows that perinatal anoxia in combination with sensorimotor restriction of the hindlimbs during infancy significantly impacts the body phenotype of rats, reducing body weight and body length during the neonatal period. Previous studies have also observed such effects in rats during exposure to a CP model (da Silva et al, 2016;Lacerda et al, 2017;Lacerda, Manhães-de-Castro, Gouveia, et al, 2019). Lacerda, Manhães-de-Castro, Gouveia et al (2019) suggested that the model's impact on these parameters may be related to motor deficits that impair access to lactation and food.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also observed such effects in rats during exposure to a CP model (da Silva et al, 2016;Lacerda et al, 2017;Lacerda, Manhães-de-Castro, Gouveia, et al, 2019). Lacerda, Manhães-de-Castro, Gouveia et al (2019) suggested that the model's impact on these parameters may be related to motor deficits that impair access to lactation and food. The model may also impair suction in the first days of postnatal life and the functionality of chewing after weaning (Lacerda et al, 2017;Lacerda, Manhãesde-Castro, Gouveia, et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, neurological deficits after an HI event leads to numerous neurological impairments including mental retardation, learning disabilities, attention‐deficit hyperactivity disorder, autism, depression, epilepsy, and cerebral palsy (Logitharajah et al, 2009). Early brain damage is associated to cerebral palsy, which is a major cause of physical disability, and results from nonprogressive brain injury before, during or after birth (Lacerda et al, 2019; Visco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%